Greening the Cement Industry in Egypt: Exploring Decarbonisation Policies for the Cement Industry - Elghamrawi, Saleh (AUC Knowledge Fountain, 2023)
The cement industry is a major contributor to global greenhouse gas emissions, accounting for approximately 7% of carbon dioxide (CO2) emissions. Cement is the most consumed material on earth, second only to water, and its demand is fueled by continuous urbanization and the lack of alternative materials. In Egypt, the cement sector is responsible for 14% of CO2 emissions, emitting over 800 kilograms of CO2 per ton of cement, surpassing the global average of 600. In 2016, Egypt ratified the Paris agreement to address climate change and has committed in its National Determined Contributions (NDC) to reduce CO2 emissions. However, progress towards reducing CO2 emissions in the cement industry has been unguided and slow. This study thus investigates the potential for a green transition in Egypt's cement industry. The study aims to identify barriers to transition, explore opportunities, and propose policy changes to accelerate the reduction of carbon emissions in cement. Utilizing a qualitative approach, this research combines in-depth interviews with experts and senior executives along with content analysis of literature and industry reports to assess the current state of Egypt's cement industry and its current decarbonisation policies. Interviews with experts highlight the presence of significant challenges such as the absence of carbon policies that can provide appropriate incentives and penalties, in addition to financing difficulties. The study highlights several opportunities for reducing carbon emissions, including the utilization of alternative fuels and raw materials, the implementation of more efficient production processes and utilization of renewable energy sources. The research explores the potential for sizable CO2 reductions in the cement industry while creating a market for waste management and utilization, as well as renewable energy sources. Finally, policy recommendations are provided for industry stakeholders to address needed carbon reforms and invites further research in the areas of cement demand and waste management value chains.